2021
DOI: 10.3389/fmolb.2021.632837
|View full text |Cite
|
Sign up to set email alerts
|

A Five Immune-Related lncRNA Signature as a Prognostic Target for Glioblastoma

Abstract: Background: A variety of regulatory approaches including immune modulation have been explored as approaches to either eradicate antitumor response or induce suppressive mechanism in the glioblastoma microenvironment. Thus, the study of immune-related long noncoding RNA (lncRNA) signature is of great value in the diagnosis, treatment, and prognosis of glioblastoma.Methods: Glioblastoma samples with lncRNA sequencing and corresponding clinical data were acquired from the Cancer Genome Atlas (TCGA) database. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…It is concentrated in the cytoplasm of CRC cells and reversely regulates miR-1287-5p expression, which indicates adverse outcomes [49]. Recent studies have also shown that PRKCQ-AS1, as an immune-related lncRNA, provides a reliable prognostic indicator for glioblastoma patients [50]. (4) LINC00957 is signi cantly related to poor OS of CRC patients upon increased expression (P < 0.05), and inhibiting LINC00957 expression can reverse 5-FU resistance via P-gP down regulation [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is concentrated in the cytoplasm of CRC cells and reversely regulates miR-1287-5p expression, which indicates adverse outcomes [49]. Recent studies have also shown that PRKCQ-AS1, as an immune-related lncRNA, provides a reliable prognostic indicator for glioblastoma patients [50]. (4) LINC00957 is signi cantly related to poor OS of CRC patients upon increased expression (P < 0.05), and inhibiting LINC00957 expression can reverse 5-FU resistance via P-gP down regulation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Pearson coefficient (r) was applied to indicate the correlation between genes and reflect the biological relationship between the two genes. MTFR2 co-expressed genes were screened in 535 cases of LUAD tissues from TCGA via the R (version 3.6.1) [29]. Screening criteria: P < 0.001 and Pearson coefficient (r > 0.4 or r < − 0.4), were defined as moderate or above.…”
Section: Screening Of Mtfr2 Co-expressed Genesmentioning
confidence: 99%
“…The genes were arranged according to the degree of differential expression by GSEA (version 4.0.1) to explore the effect of MTFR2 on each gene. Each analysis was repeated 1000 times [29,31]. Screening criteria: NOM p < 0.05.…”
Section: Go Kegg and Gseamentioning
confidence: 99%
“… Han et al (2020) reported that MIR22HG was a critical inducer of the Wnt/β-catenin signaling pathway for glioblastoma, and a specific small-molecule inhibitor, AC1L6JTK, could cause the inhibition of tumor growth in vivo . Interestingly, MIR22HG was also enlisted in an immune-related lncRNA signature associated with glioblastoma prognosis, indicating its pathophysiological complexity in this malignancy ( Li X. et al, 2021 ). Together, abundant evidence has revealed that lncRNAs play critical roles in multiple aspects of glioblastoma biology.…”
Section: Long Non-coding Rnas Implications In Various Brain Tumorsmentioning
confidence: 99%